2013
DOI: 10.1080/03601277.2013.802182
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions Concerning Intergenerational Education from the Perspective of Participants

Abstract: This article presents an evaluation of an intergenerational education experience at the University of Castilla-La Mancha (Spain). For this evaluation, following a review of the literature regarding the state of the issue, we undertake an analysis of benefits and disadvantages from the perspective of the participants. Among the benefits we find that the majority of those questioned would repeat the program, and that classroom atmosphere improved notably. Participants listed the exceptional nature of the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…While Castro et al (2014) found that intergenerational education had positive outcomes for both the younger and older adults, their study was conducted in a gerontology specific class.…”
Section: Intergenerational Educationmentioning
confidence: 99%
“…While Castro et al (2014) found that intergenerational education had positive outcomes for both the younger and older adults, their study was conducted in a gerontology specific class.…”
Section: Intergenerational Educationmentioning
confidence: 99%
“…A review of intergenerational case studies across the United Kingdom led by the Beth Johnson Foundation documented a network of over 850 organisations and practitioners who are actively involved in delivering intergenerational programmes [10]. Specifically, studies of intergenerational programmes in education (including technology) generally point to a positive impact such programmes have had on the participants, such as fostering more positive attitudes toward older adults [11]; improving older people's sense of self-worth, health and well-being [12]; improving classroom atmosphere [13], and a higher overall level of social integration [14].…”
Section: Intergenerational Education Programmesmentioning
confidence: 99%